PERAN KONSELOR MELALUI BIMBINGAN KELOMPOK DALAM MENINGKATKAN KEMATANGAN EMOSI SISWA SMA KATOLIK SANTO BONAVENTURA MADIUN - Sri Rahayu, Dwi; Yeni Susilaningsih, Chaterin (Widya Warta, 2019)
This study aimed to: 1) determine the emotional maturity level of Santo Bonaventura Catholic High School students in Madiun City, 2) describe the extent to which the role of counselors through counseling could improve the emotional maturity of class 11 of SMA Santo Bonaventura senior high school in Madiun City. The design of this study used experimental research methods; one group of students were pre-tested, treated, and post-tested; afterwards, before and after conditions were compared. The samples in this study were 10 students who had low emotional maturity scores. This study also used quantitative analysis with the Standard formula for the Mean Difference (t-test) to find the mean difference before and after being given treatment through group guidance. The results of this study used the Paired T Test. The result of the average emotional maturity of students after being given group guidance was 58.22, whereas the average before being given group guidance was 52.66. Based on table 4.6, the result of statistical calculations obtained by the value of t count was -2.992. The probability value was 0.017 <0.05. Accordingly, it can be stated that Ho is rejected and Ha is accepted, which means the role of counselor through group guidance can increase students' emotions.